The Mechanism of Yaw Torque Compensation in the Human and Motion Design for Humanoid Robots. (21st January 2013) - Zhang, Si; Huang, Qiang; Wang, Huaping; Xu, Wei; Ma, Gan; Liu, Yunhui; Yu, Zhangguo
When a humanoid robot walks fast or runs, the yaw torque is so large that the supporting foot slips easily and the robot may become unstable. The compensation for the yaw torque is important for fast humanoid walking and many studies have been focusing on yaw torque compensation. However, the issue of humanoid robot motion design that can make the movements of the robot more human-like, as well as guarantee the stability of the robot, has not been studied in-depth. In this paper, the mechanism of yaw torque compensating for human walking is firstly studied. Then we propose a method to compensate yaw torque for a humanoid robot through the motion of the arms and waist joint based on the human yaw torque compensation mechanism and ZMP stability citation. Finally, the effectiveness of the proposed method is demonstrated by the results from the simulation and walking experiments on the newly developed BHR humanoid robot.